2006
DOI: 10.1128/jvi.80.1.95-107.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Equine Herpesvirus 1 UL20 Product Interacts with Glycoprotein K and Promotes Egress of Mature Particles

Abstract: The aim of the present study was to identify and functionally characterize the equine herpesvirus 1 (EHV-1) UL20 protein (UL20p). Using a specific antiserum, UL20p was shown to be associated with membranes of infected cells, as well as with envelopes of purified virions. By Western blot analysis, UL20p was detected in two main forms exhibiting M r s of 25,000 and 75,000. Both moieties did not enter the separating gel after heating of protein samples to 99°C. The slower-migrating form of UL20p contains N-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Importantly, detailed confocal colocalization experiments have shown a strong interdependence of gK and UL20p for intracellular transport, cell surface expression and localization at the TGN, virus-induced cell fusion, and cytoplasmic virion envelopment, suggesting physical interactions between gK and UL20p (11,12,14,18,31). Additional evidence for the formation of heterodimeric or multimeric structures of gK with UL20p was obtained with equine herpesvirus type 1-infected cells (20).…”
mentioning
confidence: 80%
“…Importantly, detailed confocal colocalization experiments have shown a strong interdependence of gK and UL20p for intracellular transport, cell surface expression and localization at the TGN, virus-induced cell fusion, and cytoplasmic virion envelopment, suggesting physical interactions between gK and UL20p (11,12,14,18,31). Additional evidence for the formation of heterodimeric or multimeric structures of gK with UL20p was obtained with equine herpesvirus type 1-infected cells (20).…”
mentioning
confidence: 80%
“… b Function is assigned primarily from published data for proteins of herpes simplex virus 1 (HSV-1) ( 23 , 43 , 44 ). The discovery and function of EHV-1 IR2 ( 25 , 26 ), IR3 ( 27 29 ), UL1 and UL2 ( 39 ), UL3 ( 45 ), UL11 ( 46 ), UL20 ( 47 ), UL31 ( 48 ), UL34 ( 49 ), US4 (gp2) ( 50 ), and US6 (gI) and US7 (gE) ( 37 ) were reported previously . –, not present .…”
Section: Resultsmentioning
confidence: 55%
“…The findings that the vL11ΔIR showed reduced plaque size and delayed growth in RK13 cells clearly suggest that the deletion of sequences including the genes within the IR affects the biological properties of EHV-1 in cell culture. Previous studies showed that the EHV-1 Us4, Us6, Us7, UL6, UL10, and UL20 gene products are involved in cell-to-cell spread of virus and virus egress (Frampton et al, 2002; Guggemoos et al, 2006; Neubauer and Osterrieder, 2004; Osterrieder et al, 1996a; von Einem et al, 2004), but none of these genes is located within sequences deleted here. The smaller plaque size and delayed growth of vL11ΔIR as compared to the parent virus may be explained by the roles of EHV-1 major regulatory genes IE and IR4 that are located within both inverted repeats (Grundy et al, 1989; Holden et al, 1994; Telford et al, 1992).…”
Section: Discussionmentioning
confidence: 69%